Effects of gamma irradiation on egg hatchability, pupation, and adult emergence of the immature stages of the oriental fruit fly, Bactrocera dorsalis (hendel) (diptera: tephritidae) from Malaysia - Suhana Y.,; Mohd Shamsudin O.,; Sulaiman Z.,; Ahmad Zainuri M.D.,; Hasan S.,; Yaakop S., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Studies on the effect of irradiation on egg hatchability, pupation and adult emergence of the immature stages of the Oriental Fruit Fly, Bactrocera dorsalis (Hendel) was conducted in Malaysian Nuclear Agency, Dengkil, Selangor, Malaysia using a Co-60 source. Eggs, 1st instars to 3rd instars larvae and pupae stages were treated separately with dosages 50Gy to 400Gy to determine the most tolerance stage and the optimum dose for provide quarantine security. Each treatment involves a minimum of 100 individuals for each dose with four replications. The hatch from eggs to 1st instar larvae, pupation from eggs and all of three instars larvae to pupae, and eclosion from pupae to adult, were used as criteria to determine the effect of irradiation. Egg hatch was completely inhibited by 100Gy for early egg and 300Gy for late eggs. Dose of 200Gy and 250Gy were able to prevent completely pupation when treated from egg stage and 1st instar larvae, respectively. Unfortunately, those dosages did not affect pupation when applied to 2nd and 3rd instars, but it did prevent any from emerging as adults. Adult emergence was 100% prevented when eggs and all larvae were treated at 100Gy as compared to pupae was not completely prevented even by 400Gy. Among the four immature stages of B. dorsalis, the 3rd instar larvae (inside fruits) and pupae (outside fruits) were found to be the most tolerance stage and the early eggs are the most susceptible stage to irradiation. Our results suggest that minimum dose 100 to 150Gy is sufficient to provide a high level of quarantine security against this important pest and the dose might allow for irradiation be accepted as a quarantine treatment for most tropical fruits from Malaysia.